Geoeconomics meets geopolitics: China's new economic and foreign policy initiatives - Hanns Günther Hilpert; Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2015)
China's new leadership has launched a series of foreign policy and economic initiatives whose implications reach far beyond their own region. Washington disapproves of Beijing's plans, regarding the proposed financial institutions in particular as a challenge to their established Western-dominated counterparts. China's response is that these are sensible and important additions to the existing architecture. European states failed to fall in line with the US stance, and many became founding members of the Asian Infrastructure Investment Bank (AIIB). China's overarching vision of "new Silk Roads" integrating Asia and Europe by land and sea also demands a European response. In order to achieve better coordination than they managed over the AIIB question, the European Union and European states need to discuss and evaluate the economic and political dimensions of the Chinese initiatives in their overall context. (SWP Comments)
Keywords: 320